Reverse phase-liquid chromatography assisted protocol for simultaneous determination of lamivudine and tenofovir disoproxil fumarate in combined medication used to control HIV infection: an investigative approach - Vaibhav S. Adhao; Suraj R. Chaudhari; Jaya P. Ambhore; Sunil Sangolkar; Raju R. Thenge; Rameshwar S. Cheke; Amod S. Patil (SpringerOpen, 2021)
Abstract Background Human immunodeficiency virus (HIV) causes severe life-threatening condition, i.e., AIDS. HIV destabilises an individual's ability to prevent infection. Therefore, the combine medication lamivudine (LVD) and tenofovir disoproxil fumarate (TDF) are prescribed to suppress the amount of HIV infection in individual's body; thus, the individual's immune system could function properly. Consequently, the objective of present research work was to investigate robust and sensitive liquid chromatography avenue for simultaneous determination of lamivudine and tenofovir disoproxil fumarate in pure material and combined dosage form. Results The reversed-phase chromatographic separation has been performed through Hypersil BDS C18 column using solvent system composed of 10 mM potassium dihydrogen phosphate (pH 4.0): acetonitrile (60:40% v/v). The determination was executed at 30 oC at 1 mL/min rate for flow of solvent system through column. The eluents of column were monitored at 265 nm using Photodiode Array detector has revealed admirable retention times, i.e., 4.67 and 8.78 min for both drugs, respectively. The calibration curve demonstrated excellent linearity in the range of 10-50 μg/mL for lamivudine and tenofovir disoproxil fumarate with better determination coefficients was more than (r 2 0.999). Conclusion The estimable method was effectively validated with respect to accuracy, precision, sensitive (limit of detection and limit of quantitation), robustness, ruggedness, and for selectivity and specificity. The value less than 2 for percentage relative standard deviation for accuracy, precision, robustness, and ruggedness satisfying the acceptance criteria as per procedure of International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use.